World Bank Research Digest, Vol. 12(1) - World Bank (World Bank, Washington, DC, 2019)
This issue includes the following headings: Realizing Education's Promise; Investing in School Readiness; Can Participation by Parents Improve School Quality? Does More Time in School ImproveLearning Outcomes for Students? How Does Partnering with the Government Affect Low-Cost Private Schools? Making Teachers Better: What We Know and How to Learn More; Improving Service Delivery for Better Education and Health Outcomes in Uganda; Building More Schools: The Effects onEquality of Opportunity in Education; Predicting School Dropouts in Guatemala and Honduras; Teachers’ Effectiveness in Pakistan and the Link to Wages; and Going Beyond Schooling to ImproveWorkforce Skills.